A Paradox of Synergy: Contagion and Capacity Effects in Mergers and Acquisitions - Shaver, J. Myles (Academy of Management Review, 2006)
Integrating merged businesses to realize synergies can adversely affect the distribution of potential outcomes through two mechanisms: the contagion effect and the capacity effect. I describe these effects, highlight when they will be pronounced, and discuss their importance. My arguments demonstrate that an inherent element of synergy-based mergers and acquisitions is that actions to facilitate synergy capture can amplify threats and can inhibit firms' ability to respond to favorable conditions in the business environment.